More language(s) - more space(s)? Reflections on the representation of heteroglossia and minority languages in the Alpe-Adria Region - Zerzer, Nada (Annales. Series historia et sociologia, 2009)
This article addresses the issue how heteroglossic people in the three regions of Carinthia, Primorska, and the Trst/Trieste region experience their multilingualism and its representations in everyday day life. The approach is transdisciplinary and includes theory and methods from fields of political theory, sociology of space, sociolinguistics, ethnography, visual cultures and multimodal discourse analysis. The research focus is on social constructions of space, created by heteroglossic people in their everyday life and by the representations of the languages in their living environment. This article wants to take a closer look at life with - or in - heteroglossia and at possible integrative handling of it
Keywords: Alpe-Jadran; družba; družbeni odnosi; javni prostor; jezikovne manjšine; narodne manjšine; society; večjezičnost; vizualna kultura